THE EFFECT OF MORINGA LEAVES FLOUR AND ROASTING TIME ON THE QUALITY OF COOKIES MOCAF (Modified Cassava Flour) - Budi Suarti; Evan Ardyanto AS; Masyhura MD , (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
This study aims to determine the effect of addition moringa leaf powder and long roasting on the quality of biscuit from mocaf. The research uses Complete Randomized Design (CRD) factorial with (2) two replication. Factor I is addition of moringa leaf powder with password (T) which consists of 4 standard, namely : T0 = 0%, T1 = 3%, T2 = 6%, and T3 =9%. Factor II is long roasting with password (L) which consists of 4 standard, namely : L1 = 5 minute, L2 = 10 minute, L3 = 15 minute, and L4 = 20 minute. Parameter analyzed were : protein, carbohydrate, organoleptic : colour, aroma, and taste. Statistical analysis result on each parameter gives the following conclusion : the higest protein 7,096% in treatment T3 and the lowest protein 5,827% in treatment T0. The higest protein 7,233% in treatment L4 and the lowest protein 5,982% in treatment L1. The higest carbohydrate 69,408% in teratment T3 and the lowest carbohydrate 68,620% in treatment T0. The higest carbohydrate 69,225% in teratment L4 dan the lowest carbohydrate 68,782% in treatment L1. The higest colour 3,575 in treatment T0 and the lowest colour 3,062 in treatment T3. The higest colour 3,512 in teratment L4 and lowest colour 3,062 in treatment L1. The higest aroma 3,286 in treatment T0 and lowest aroma 2,362 in treatment T3. The higest aroma 2,998 in treatment L4 and the lowest aroma 2,640 in treatment L1. The higest taste 4,980 in treatment T0 and the lowest taste 2,552 in treatment T3. The higest taste 3,205 in treatment L4 and the lowest taste 2, 846 in treatment L1.Keyword : Cassava, moringa leaves, mocaf.